Safety and efficacy of epigallocatechin gallate in multiple system atrophy (PROMESA): a randomised, double-blind, placebo-controlled trial. Issue 8 (August 2019) - Levin, Johannes; Maaß, Sylvia; Schuberth, Madeleine; Giese, Armin; Oertel, Wolfgang H; Poewe, Werner; Trenkwalder, Claudia; Wenning, Gregor K; Mansmann, Ulrich; Südmeyer, Martin; Eggert, Karla; Mollenhauer, Brit; et al.
Summary: Background: Multiple system atrophy is a rare neurodegenerative disease characterised by aggregation of α-synuclein in oligodendrocytes and neurons. The polyphenol epigallocatechin gallate inhibits α-synuclein aggregation and reduces associated toxicity. We aimed to establish if epigallocatechin gallate could safely slow disease progression in patients with multiple system atrophy. Methods: We did a randomised, double-blind, parallel group, placebo-controlled clinical trial at 12 specialist centres in Germany. Eligible participants were older than 30 years; met consensus criteria for possible or probable multiple system atrophy and could ambulate independently (ie, were at Hoehn and Yahr stages 1–3); and were on stable anti-Parkinson's, anti-dysautonomia, anti-dementia, and anti-depressant regimens (if necessary) for at least 1 month. Participants were randomly assigned (1:1) to epigallocatechin gallate or placebo (mannitol) via a web-generated permuted blockwise randomisation list (block size=2) that was stratified by disease subtype (parkinsonism-predominant disease vs cerebellar-ataxia-predominant disease). All participants and study personnel were masked to treatment assignment. Participants were given one hard gelatin capsule (containing either 400 mg epigallocatechin gallate or mannitol) orally once daily for 4 weeks, then one capsule twice daily for 4 weeks, and then one capsule three times daily for 40 weeks. After 48 weeks, all patients underwent a 4-week wash-out period. The primary endpoint was change in motor examination score of the Unified Multiple System Atrophy Rating Scale (UMSARS) from baseline to 52 weeks. Efficacy analyses were done in all people who received at least one dose of study medication. Safety was analysed in all people who received at least one dose of the study medication to which they had been randomly assigned. This trial is registered withClinicalTrials.gov (NCT02008721 ) and EudraCT (2012-000928-18), and is completed. Findings: Between April 23, 2014, and Sept 3, 2015, 127 participants were screened and 92 were randomly assigned—47 to epigallocatechin gallate and 45 to placebo. Of these, 67 completed treatment and 64 completed the study (altough one of these patients had a major protocol violation). There was no evidence of a difference in the mean change from baseline to week 52 in motor examination scores on UMSARS between the epigallocatechin gallate (5·66 [SE 1·01]) and placebo (6·60 [0·99]) groups (mean difference −0·94 [SE 1·41; 95% CI −3·71 to 1·83]; p=0·51). Four patients in the epigallocatechin gallate group and two in the placebo group died. Two patients in the epigallocatechin gallate group had to stop treatment because of hepatotoxicity. Interpretation: 48 weeks of epigallocatechin gallate treatment did not modify disease progression in patients with multiple system atrophy. Epigallocatechin gallate was overall well tolerated but was associated with hepatotoxic effects in some patients, and thus doses of more than 1200 mg should not be used. Funding: ParkinsonFonds Deutschland, German Parkinson Society, German Neurology Foundation, Lüneburg Foundation, Bischof Dr Karl Golser Foundation, and Dr Arthur Arnstein Foundation.